Training participation and its impact on productivity and wage : empirical analysis of knowledge workers in MSC Malaysia - Zulkifli, Izyani (2009)
Using data from an online survey of knowledge workers within MSC Malaysia, this study (1) compares training participation between knowledge workers at local and foreign MSC-status companies and (2) examines the impact of this participation on productivity and wage levels. A cross tabulation analysis, logistic regression model and OLS regression corrected for selectivity bias are used for these purposes. The study finds that participation in training is generally higher among knowledge workers who are employed by foreign MSC-status companies. Certain aspects of training participation are positively correlated with productivity level, namely, in-house training, direct training and the number of training sessions attended. However, participation in foreign training in the past and longer duration of training are associated with a negative impact on productivity level. As for the wage effects of training, result shows that training participation has a positive impact on the KWs’ wage level but the association is only significant after selectivity bias is taken into account.